Water Budget and Precipitation Efficiency of Typhoon Morakot (2009) - Huang, Hsiao-Ling; Yang, Ming-Jen; Sui, Chung-Hsiung (Journal of the atmospheric sciences, 2014)
In this study, the Weather Research and Forecasting model, version 3.2, with the finest grid size of 1 km is used to explicitly simulate Typhoon Morakot (2009), which dumped rainfall of more than 2600 mm in 3 days on Taiwan. The model reasonably reproduced the track, the organization, the sizes of the eye and eyewall, and the characteristics of major convective cells in outer rainbands. The horizontal rainfall distribution and local rainfall maximum in the southwestern portion of the Central Mountain Range (CMR) are captured. The simulated rain rate and precipitation efficiency (PE) over the CMR are highly correlated. In the absence of terrain forcing, the simulated TC’s track is farther north and rainfall distribution is mainly determined by rainbands. The calculated rain rate and PE over the CMR during landfall are about 50% and 15%–20% less than those of the full-terrain control run, respectively. By following major convective cells that propagate eastward from the Taiwan Strait to the CMR, it is found that the PE and the processes of vapor condensation and raindrop evaporation are strongly influenced by orographic lifting; the PEs are 60%–75% over ocean and more than 95% over the CMR, respectively. The secondary increase of PE results from the increase of ice-phase deposition ratio when the liquid-phase condensation becomes small as the air on the lee side subsides and moves downstream. This nearly perfect PE over the CMR causes tremendous rainfall in southwestern Taiwan, triggering enormous landslides and severe flooding.